What should dental services for people with disabilities be like? Results of an irish delphi panel survey. - MAC GIOLLA PHADRAIG, CAOIMHIN; NUNN, JUNE; DOUGALL, ALISON (My University, 2014)
BACKGROUND: This study aimed to generate prioritised goals for oral health services for people with disabilities as a first step in meeting the need for evidence based oral health services for people with disabilities in Ireland. METHODS: The study used a three round modified e-Delphi method, involving dental service professionals and people with disabilities or their representatives, in Ireland. Three rounds were completed online using SurveyMonkey. Round 1 asked: "List what you think dental services for people with disabilities in Ireland should be like." Items for subsequent rounds were generated from responses to Round 1. Round 2 and Round 3 used 5 point Likert scales to rank these items by priority: from No Priority (1) to Top Priority (5). Consensus was achieved on each item where at least 80% of respondents considered an item either High or Top Priority. A consensus meeting concluded the process. RESULTS: Sixty-one panelists started and 48 completed the survey. The Delphi panel agreed on level of priority for 69 items and generated 16 consensus statements. These statements covered a range of topics such as access to care, availability of information and training, quality of care, dental treatment and cost. A recurrent theme relating to the appropriateness of care to individual need arose across topics suggesting a need to match service delivery according to the individual's needs, wants and expectations rather than the disability type/diagnosis based service which predominates today. CONCLUSIONS: This process produced a list of prioritised goals for dental services for people with disabilities. This creates a foundation for building evidence-based service models for people with disabilities in Ireland.
PUBLISHED
Keywords: Dental services